Building and codifying the measure of preferred psychological characteristics for admission to sports education - Dr. Aseel Naji M. Suha Darweesh (الرياضة المعاصرة)
The psychological requirements are one of the most important of these requirements that contribute to achieving high sports levels, and of great benefit in the field of building the abilities of the player and developing and improving his individual abilities, which determines the behavior of his performance and through the follow-up of the researcher to the level of admissions of the Faculty of Sports Education in measuring the psychological characteristics of acceptance in sports education depends on personal diligence and the corresponding, note that most coaches did not give sufficient attention in the psychological aspect through some psychological features characterized by each student and the development of those psychological abilities and find new ways to measure, Waste of effort and time in training and then not achieving the required level and results 0Research aims to build and codify the measure of preferred psychological characteristics for admission to the Faculty of Sports Education. The descriptive method was used in the survey method to suit the nature of the problem and be caused by the best means and means to reach the correct results of the search and collect the required information and data. The researchers chose the research sample from the 80 applicants from the Faculty of Physical Education, Al Muthanna University, which concluded that the measure of the preferred psychological characteristics of students of the Faculty of Physical Education and Sports Sciences / Muthanna University proved its validity on the research sample.